PERANCANGAN FILM ANIMASI 2D CERITA RAKYAT SAMBAS ”PERISTIWA DI TANJUNG DATOK” DENGAN METODE MDLC - Agung Damar Jati; Yuda; Noferianto Sitompul; Narti Prihartini; Naufal Aulia Fiermeiza; Vanie Wijaya; U Heri Mulyanto; Lang Jagat; Sri Wahyuni; Erifa Syahnaz (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Temajuk Village, located in Paloh District, Sambas Regency, West Kalimantan, boasts a unique natural landscape, culture, and rich history. One important part of this village's cultural heritage is the folktale "The Events at Tanjung Datok," which contains moral values, local wisdom, and the philosophy of life of the local community. Unfortunately, this story is still limited to oral tradition and has not been visually documented. The lack of interest in literacy among some Sambas residents means that knowledge of this story remains limited to the community around Tanjung Datok. Until now, the story has not been transformed into a more effective medium to keep up with current developments so that it can reach a wider audience, one of which is through 2D Animation visualization. The development method used in making 2D animated films is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collection, production, testing, and distribution. This method was chosen because it is able to provide a systematic and structured approach to the animation production process. The creation of a 2D animated film of Sambas folklore entitled "Events in Tanjung Datok" aims to document and visualize the Sambas folklore located in Tanjung Datok in the form of a 2D animated film. This animated media is expected to be an educational resource that can increase public understanding of local history and culture. This research is expected to produce an interesting and informative 2D animation, so that the moral message and cultural values ​​of the story "Events in Tanjung Datok" can be conveyed effectively to the audience, while strengthening the local cultural identity of Temajuk Village. Based on the questionnaire test results using the Likert scale technique, conducted on two material experts and two media experts, with a total score of 81% and 97% respectively. In addition, the questionnaire was also tested on 30 members of the general public with a score of 93%. Based on the test results, it can be concluded that, in general, respondents gave a very good assessment, and this film is worthy of publication. It is hoped that it can later become an educational medium that can be used by the public, especially in the world of education.